Enhanced airway hyperresponsiveness in asthmatic children and mice with A(H1N1)pdm09 infection. Issue 2 (20th January 2021) - Ariyoshi, Taira; Tezuka, Junichiro; Yasudo, Hiroki; Sakata, Yasufumi; Nakamura, Tamaki; Matsushige, Takeshi; Hasegawa, Hideki; Nakajima, Noriko; Ainai, Akira; Oga, Atsunori; Itoh, Hiroshi; Shirabe, Komei; et al.
Abstract: Background: Severe asthma exacerbation is an important comorbidity of the 2009 HIN1 pandemic (A(H1N1)pdm09) in asthmatic patients. However, the mechanisms underlying severe asthma exacerbation remain unknown. In this study, airway hyperresponsiveness (AHR) was measured in pediatric asthma patients infected with A(H1N1)pdm09. We also evaluated AHR in asthmatic mice with A(H1N1)pdm09 infection and those with seasonal influenza for comparison. Methods: AHRs in asthmatic children were defined as the provocative acetylcholine concentration causing a 20% reduction in forced expiratory volume in 1 s (PC20 ). To investigate the pathophysiology using animal models, BALB/c mice aged 6‐8 weeks were sensitized and challenged with ovalbumin. Either mouse‐adapted A(H1N1)pdm09, seasonal H1N1 virus (1 × 10 5 pfu/20 μl), or mock treatment as a control was administered intranasally. At 3, 7, and 10 days after infection, each group of mice was evaluated for AHR by methacholine challenge using an animal ventilator, flexiVent. Lung samples were resected and observed using light microscopy to assess the degree of airway inflammation. Results: AHRs in the children with bronchial asthma were temporarily increased, and alleviated by 3 months after discharge. AHR was significantly enhanced in A(H1N1)pdm09‐infected asthmatic mice compared to that in seasonal H1N1‐infected mice ( p  < .001), peaking at 7 days postinfection and then becoming similar to control levels by 10 days postinfection. Histopathological examination of lung tissues showed more intense infiltration of inflammatory cells and severe tissue destruction in A(H1N1)pdm09‐infected mice at 7 days postinfection than at 10 days postinfection. Conclusion: Our results suggest that enhanced AHR could contribute to severe exacerbation in human asthmatic patients with A(H1N1)pdm09 infection. Abstract : AHR was significantly enhanced in asthmatic mice with A(H1N1)pdm09 infection compared with seasonal influenza infection. AHR and pulmonary inflammation of A(H1N1)pdm09‐infected mice showed peak at 7 days post infection and they were improved by 10 days postinfection. Also, AHR in asthmatic children after A(H1N1)pdm09 infection were temporarily increased, and alleviated by 3 months after discharge.